2021
DOI: 10.1136/bmj.n1585
|View full text |Cite|
|
Sign up to set email alerts
|

Optimizing Therapy to Prevent Avoidable Hospital Admissions in Multimorbid Older Adults (OPERAM): cluster randomised controlled trial

Abstract: Objective To examine the effect of optimising drug treatment on drug related hospital admissions in older adults with multimorbidity and polypharmacy admitted to hospital. Design Cluster randomised controlled trial. Setting 110 clusters of inpatient wards within university based hospitals in four European countries (Switzerland, Netherlands, Belgium, and Republic of Ireland) defined by attending hospital doc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
140
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 108 publications
(161 citation statements)
references
References 57 publications
8
140
0
2
Order By: Relevance
“…In addition, our geriatric population was relatively functionally independent, with only 8.4% of participants living in nursing homes. Results from a study investigating the impact of STOPP/START criteria (v1) in frail geriatric chronic care residents found that 82.4% of STOPP and 92.6% of START recommendations made by a research pharmacist were implemented by the attending physician [ 28 , 29 ], whereas only 62.2% of all OPERAM patients had one or more STOPP/START recommendations implemented at 2-month follow-up [ 30 ]. Interestingly, implementation of recommendations to discontinue benzodiazepines was lower in the geriatric chronic care setting (23%; n = 3/13) than in the OPERAM trial at 2-month follow-up (39.1%; n = 45/115) [ 28 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, our geriatric population was relatively functionally independent, with only 8.4% of participants living in nursing homes. Results from a study investigating the impact of STOPP/START criteria (v1) in frail geriatric chronic care residents found that 82.4% of STOPP and 92.6% of START recommendations made by a research pharmacist were implemented by the attending physician [ 28 , 29 ], whereas only 62.2% of all OPERAM patients had one or more STOPP/START recommendations implemented at 2-month follow-up [ 30 ]. Interestingly, implementation of recommendations to discontinue benzodiazepines was lower in the geriatric chronic care setting (23%; n = 3/13) than in the OPERAM trial at 2-month follow-up (39.1%; n = 45/115) [ 28 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Results from a study investigating the impact of STOPP/START criteria (v1) in frail geriatric chronic care residents found that 82.4% of STOPP and 92.6% of START recommendations made by a research pharmacist were implemented by the attending physician [ 28 , 29 ], whereas only 62.2% of all OPERAM patients had one or more STOPP/START recommendations implemented at 2-month follow-up [ 30 ]. Interestingly, implementation of recommendations to discontinue benzodiazepines was lower in the geriatric chronic care setting (23%; n = 3/13) than in the OPERAM trial at 2-month follow-up (39.1%; n = 45/115) [ 28 , 30 ]. These differences may illustrate that decisions to optimise pharmacotherapy in a hospitalised population are likely to differ from decisions made for long-term care facility residents or in primary care.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A major strength of this study is its high feasibility due to the follow-up of 822 already included multimorbid participants with strong strategies of containment of loss to follow-up. 22 Notably, individuals with cognitive impairment were included, who are commonly excluded from studies. In addition to the development and internal validation of the LE estimator, we also assess its implementation and clinical usability.…”
Section: Perspectivementioning
confidence: 99%
“…Therefore, the lack of knowledge and skills in ELSI may, in turn, lead to suboptimal medical practice towards vulnerable groups. In fact, contemporary data on drug misuse ( Culberson and Ziska, 2008 ), polypharmacy linked to multimorbidity ( Blum et al, 2021 ), inappropriate and/or non-evidence-based self-medication ( Yousef et al, 2008 ; Rather et al, 2017 ), misdosing ( Nemati et al, 2016 ), inappropriate prescription trends ( Hovstadius et al, 2014 ; Moriarty et al, 2015 ) (both hold true especially in the elderly), and mortality and morbidity outcomes in relation to drug overuse such as for opioids ( Cheatle, 2015 ), alongside suboptimal medical practice ( Ma et al, 2005 ; Massey et al, 2009 ), reinforce more than ever the call-to-action for developing Social Pharmacology courses to address these alarming issues.…”
Section: Introductionmentioning
confidence: 99%